2012
DOI: 10.1111/j.1551-2916.2012.05244.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PMNPZT Transparent Ceramics by Two‐Stage Sintering

Abstract: Highly optically transparent ceramics of (1Àx)Pb(Mg 1/3 Nb 2/3 ) O 3 -xPb(Zr 0.53, Ti 0.47 )O 3 (PMN-PZT) were fabricated by a two-stage sintering method without La-modification. The ceramics exhibited high optical transparency (64% at 1500 nm) for visible and near infrared wavelength. The ferroelectric domain and microstructure of PMN-PZT transparent ceramics prepared were also investigated. Fully dense microstructure was observed in all PMN-PZT transparent ceramic samples. Higher PMN containing compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
1
17
0
6
Order By: Relevance
“…. This is reasonable that the FE‐like characteristic or the relatively bigger FE domain for composition A would induce an original intrinsic light scattering and thus a degradation in the high transparency in the original state, albeit a smaller E dr . This suggests a competitive relationship between the driving field E dr and the transparency in original state for these PLZT ceramics.…”
Section: Resultsmentioning
confidence: 80%
“…. This is reasonable that the FE‐like characteristic or the relatively bigger FE domain for composition A would induce an original intrinsic light scattering and thus a degradation in the high transparency in the original state, albeit a smaller E dr . This suggests a competitive relationship between the driving field E dr and the transparency in original state for these PLZT ceramics.…”
Section: Resultsmentioning
confidence: 80%
“…Figure shows the variation of transmittance of Eu‐doped 0.75PMN‐0.25PT transparent ceramics under external DC fields. It can be found that the transmittance would decrease with increasing electric field for lower Eu doping concentrations (1% and 2%) which results from the growth of ferroelectric domains since incident light could be significantly scattered by domains with large sizes . While the threshold field ( E th) for the decrease of transmitted light intensity of 1% and 2% Eu‐doped samples is different, as can be seen in the Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Possible mechanisms that increased the optical transmission by La‐doping were associated with changes in microstructure and/or domain structure . To determine which factor was more important, the microstructures were initially studied.…”
Section: Resultsmentioning
confidence: 99%